The Influence of Work-Life Balance and Employee Engagement on Performance Through Job Satisfaction - Subarto, Subarto; Solihin, Dede (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
AbstractThis research aims to analyze the impact of work-life balance and employee engagement on employee performance, proposing job satisfaction as a mediating variable. The study was conducted at PT. Nindya Karya (Persero) Region 2. The study sample comprised 220 employees. The data analysis technique uses Smart PLS to employ the Structural Equation Model (SEM). The findings highlight that work-life balance and employee engagement significantly impact both job satisfaction and performance. Moreover, job satisfaction plays a crucial role in enhancing employee performance. The relationship between work-life balance and employee engagement in performance is significantly influenced by job satisfaction as a mediating factor. Consequently, the endorsement of the mediating role of job satisfaction emphasizes its importance as a strategy for improving employee performance at PT. Nindya Karya (Persero) Region 2.